[latex] \frac{ m^{4}-1}{ m^{8}-1}[/latex], если m=1/2[latex] \frac{ x^{3}+ y^{3}}{ x^{6}- y^{6}}[/latex], если x=2, y=3

[latex] \frac{ m^{4}-1}{ m^{8}-1}[/latex], если m=1/2 [latex] \frac{ x^{3}+ y^{3}}{ x^{6}- y^{6}}[/latex], если x=2, y=3
Гость
Ответ(ы) на вопрос:
Гость
(m^2-1)(m^2+1)/(m^4-1)(m^4+1)=(m-1)(m+1)(m^2+1)/(m2-1)(m^2+1)(m^4+1)=(m-1)(m+1)(m^2+1)/(m-1)(m+1)(m^2+1)(m^4+1) теперь по-моему все сократится кроме m^4+1 получим: 1/(m^4+1)=1/(m^2+1)(m^2-1)=1/(m^2+1)(m-1)(m+1) подставим: 1/1,25*(-0,5)*1,5=1/(-0,3125)=-3,2 (x^3+y^3)/(x^3-y^3)(x^3+y^3)=1/(x^3-y^3)=1/(x-y)(x^2+xy+y^2) подставим: 1/(-1)*(4+6+9)=1/-19=-1/19
Не нашли ответ?
Ответить на вопрос
Похожие вопросы